The influence of match exposure on injury risk in elite men's rugby union. Issue 1 (January 2023) - Williams, Sean; Kay, Ella; Bryan, Richard; Lambert, Mark; Cross, Matthew; West, Stephen W.; Kemp, Simon; Stokes, Keith A.
Abstract: Objectives: To investigate the influence of previous season match exposure on injury incidence and burden in elite men's rugby union. Design: A three-season (2016–17 to 2018–19) retrospective cohort design was used to collect and analyse injury and exposure data across English Premiership rugby union teams. Methods: Generalised linear mixed-effects models were used to model the influence of match exposure (all match involvements, match involvements of ≥20 mins, and full-game equivalents) upon match and training injury incidence and burden in the following season. Results: Involvement in ≥31 matches within a season was associated with substantially increased match and training injury burden in the following season. Match exposure was not clearly associated with injury incidence in the following season. The increased match injury burden associated with higher match involvements appeared to be driven by an increased risk for older (>26 y) Forwards, whilst the increased training injury burden associated with higher match involvements appeared to be driven by an increased risk for older (>26 y) Backs. Conclusions: The present study demonstrates that all match involvements, regardless of duration, should be considered when exploring associations between match exposure and injury risk. High match involvements (≥ 31 matches) are associated with elevated injury burden, in both matches and training, in the following season. The physical and psychological load of players with high previous-season match exposure should be carefully managed.